2020
DOI: 10.3389/fpsyg.2020.00308
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of IRT Observed Score Kernel Equating and Several Equating Methods

Abstract: Item response theory (IRT) observed score kernel equating was evaluated and compared with equipercentile equating, IRT observed score equating, and kernel equating methods by varying the sample size and test length. Considering that IRT data simulation might unequally favor IRT equating methods, pseudo tests and pseudo groups were also constructed to make equating results comparable with those from the IRT data simulation. Identity equating and the large sample single group rule were both set as criterion equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…As the number of anchor items increased, the errors of the estimates in both methods were closer to one another. Wang et al (2020) also obtained similar results where the number of items was 30 and 45 in the simulation. This finding is not supported by the findings of Uysal (2014), in which he found that error estimates with the Stocking-Lord method were lower than the Haebara method.…”
Section: Error Distributionssupporting
confidence: 61%
See 1 more Smart Citation
“…As the number of anchor items increased, the errors of the estimates in both methods were closer to one another. Wang et al (2020) also obtained similar results where the number of items was 30 and 45 in the simulation. This finding is not supported by the findings of Uysal (2014), in which he found that error estimates with the Stocking-Lord method were lower than the Haebara method.…”
Section: Error Distributionssupporting
confidence: 61%
“…Öztürk-Gübeş (2019), on the other hand, investigated the effect of multidimensionality on test equating and not included the change in the item numbers. Moreover, Wang et al (2020) compared equapercentile equating, Kernel equating, and IRT Kernel equating methods.…”
Section: Error Distributionsmentioning
confidence: 99%
“…One advantage of this method is that equivalent scores are always within an interval of possible achievable scores, even though irregular score distributions are possible. 21 Therefore, to ensure a normal distribution of the test scores, log-linear smoothing of each measure's raw scores was applied leading to higher accuracy. Training and validation samples show similar results, therefore supporting our analysis.…”
Section: Conversions Of Mmse and Moca Using Equipercentile Equating M...mentioning
confidence: 99%
“…By selecting common items across two HRQOL instruments, scores of a single instrument can be compatible with the scores of the other instrument (i.e., test equating). While traditional equating methods are available on test equating, equating methods using IRT model are known for more accurate and stable [24,25,34,35]. The equating across the instruments may be a promising method.…”
Section: Discussionmentioning
confidence: 99%